ANALISIS HIPERTENSI TIDAK TERKONTROL DI UPT PUSKESMAS TELADAN KOTA MEDAN TAHUN 2021 - Siti Permata Sari Lubis; Hesti Despita Siregar; Esraida Simanjuntak (Program Studi S1/DIII-Keperawatan Universitas Imelda Medan, 2022)
Uncontrolled hypertension is a disease that can cause various organ disorders. The prevalence of hypertension in North Sumatra Province based on data from the Research and Development Agency of the Ministry of Health reaches 5.52% of the total population in North Sumatra. The prevalence of hypertension in the city of Medan is 4.97%. Data on Hypertension of the Medan City Health Office in 2019 with the number of hypertension sufferers of 38,556 people reported from 41 Puskesmas in Medan City where 59.7% of patients with hypertension were not controlled at the Exemplary Health Center. This study aims to analyze the effect of education, spouse status, stress and salt consumption on the incidence of uncontrolled hypertension. This type of research uses a cross sectional study approach with a population of 1975 people with a sample size of 92 people. The instrument used is a questionnaire with purposive sampling technique. Data analysis was performed using univariate analysis, bivariate analysis, and multivariate analysis. The results of the study showed that the variables of education (p-value 0.036), stress (p-value 0.012) and salt consumption (p-value 0.032) had an effect on the incidence of uncontrolled hypertension at UPT Puskesmas Teladan Medan City. The most dominant factor influencing the incidence of uncontrolled hypertension is stress with an OR value of 4.637 (95% CI 1.404 – 15, 312), which means that people who experience stress may be at risk of having uncontrolled hypertension 4.637 times compared to people who do not experience stress. Based on this, it can be concluded that there is an influence of education, stress and salt consumption with the incidence of uncontrolled hypertension, and the most dominant factor influencing the occurrence of uncontrolled hypertension is stress.